Optimization of Printing Parameters for Direct and Indirect Extrusion on Hydrogel 3D Printers - Nguyen, Thanh Tan; Pham, Ngoc Hieu; Nguyen, Hoai Nam; Phan, Quoc Bao; Tran, Van Tron (Management and Production Engineering Review, 2026)
Three-dimensional (3D) printing is an attractive method for creating gel geometries for specific applications. In this research, the 3D printing parameters for direct and indirect extrusion of alginate-based hydrogels are optimized using the Taguchi and Analysis of Variance methods for output responses, including printed shape retention and the height of the 3-printed layers. The results show that for an indirect extrusion, the optimal values of extrusion speed, printingspeed, and nozzle distance for the shape retention ability are 13 steps/mm, 50 mm/s, and 0.5 mm, respectively, while those values for the printed height are 13 steps/mm, 60 mm/s, and 0.5 mm, respectively. For direct extrusion, the optimal parameter set for former response is 35 steps/mm, 60 mm/s, and 0.6 mm, respectively, while the set for the latter is 35 steps/mm, 40 mm/s, and 0.6 mm, respectively. The findings in this report can be used as data for related research.